2021
DOI: 10.1101/2021.11.16.468876
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploratory methods for high-performance EEG speech decoding

Abstract: State-of-the-art technologies in neural speech decoding utilize data collected from microwires or microarrays implanted directly into the cerebral cortex. Yet as a tool accessible only to individuals with implanted electrodes, speech decoding from devices of this nature is severely limited in its implementation, and cannot be considered a viable solution for widespread application. Speech decoding from non-invasive EEG signals can achieve relatively high accuracy (70-80%), but only from very small classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…This paradigm improved subject performance in phoneme discrimination (in matched trials) by administering two closely spaced TMS pulses prior to phoneme presentation 54 . There is evidence that TMS may facilitate speech decoding when stimulation to the motor cortex target regions that control the muscles involved in the production of a specific phoneme category, and errors in decoding may be induced when stimulation occurs in an unrelated region of the motor cortex, prompting the perception of another phoneme category 51,54 . A mismatch between the phoneme type and stimulation site will introduce uncertainty into the decoding task, similar to when a phoneme is misheard in everyday speech.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This paradigm improved subject performance in phoneme discrimination (in matched trials) by administering two closely spaced TMS pulses prior to phoneme presentation 54 . There is evidence that TMS may facilitate speech decoding when stimulation to the motor cortex target regions that control the muscles involved in the production of a specific phoneme category, and errors in decoding may be induced when stimulation occurs in an unrelated region of the motor cortex, prompting the perception of another phoneme category 51,54 . A mismatch between the phoneme type and stimulation site will introduce uncertainty into the decoding task, similar to when a phoneme is misheard in everyday speech.…”
Section: Methodsmentioning
confidence: 99%
“…We recommend that the larger dataset be used for model development and that the smaller dataset be used to validate the model in more stringent conditions. Our own tests have shown that, by means of DDA, we can successfully perform a classification analysis with both data sets 51 .…”
Section: Limitations and Final Remarksmentioning
confidence: 99%
See 3 more Smart Citations